Promoting Problem Solving About Health Management: A Mixed-Methods Pilot Evaluation of a Digital Health Intervention for Older Adults With Pre-Frailty and Frailty. (January 2021) - Chen, Annie T.; Chu, Frances; Teng, Andrew K.; Han, Soojeong; Lin, Shih-Yin; Demiris, George; Zaslavsky, Oleg
Background: There is a need for interventions to promote health management of older adults with pre-frailty and frailty. Technology poses promising solutions, but questions exist about effective delivery.Objectives: We present the results of a mixed-methods pilot evaluation of Virtual Online Communities for Older Adults (VOCALE), an 8-week intervention conducted in the northwestern United States, in which participants shared health-related experiences and applied problem solving skills in a Facebook group.Methods: We performed a mixed-methods process evaluation, integrating quantitative and qualitative data, to characterize the intervention and its effects. We focus on four areas: health-related measures (health literacy and self-efficacy), participation, problem solving skills enacted, and subjective feedback.Results: Eight older adults with pre-frailty and frailty (age = 82.7 ± 6.6 years) completed the study. There was an upward trend in health literacy and health self-efficacy post-intervention. Participants posted at least two times per week. Content analysis of 210 posts showed participants were able to apply the problem solving skills taught, and exit interviews showed participants' increased awareness of the need to manage health, and enjoyment in learning about others.Conclusion: This mixed-methods evaluation provides insight into feasibility and design considerations for online interventions to promote health management among vulnerable older adults.